2019
DOI: 10.1021/acsami.9b16390
|View full text |Cite
|
Sign up to set email alerts
|

Low-Electronegativity Vanadium Substitution in Cobalt Carbide Induced Enhanced Electron Transfer for Efficient Overall Water Splitting

Abstract: Developing highly efficient electrocatalysts while revealing the active site and reaction mechanism is essential for electrocatalytic water splitting. To overcome the number and location limitations of defects in the electrocatalyst induced by conventional transition-metal atom (e.g. Fe, Co, and Ni) surface doping, we report a facile strategy of substitution with lower electronegative vanadium in the cobalt carbide, leading to larger amounts of defects in the whole lattice. The self-supported and quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…Meanwhile, Zhang et al [ 149 ] fabricated self‐supported and quantitatively substituted V 0.28 Co 2.72 C/CNFs with larger amounts via direct electrospinning. The electron transfer from V to Co made Co a local negative charge center and led to a significant increase in efficiency for overall water splitting.…”
Section: Electrospun Nanocatalysts For Electrochemical Water Splittingmentioning
confidence: 99%
“…Meanwhile, Zhang et al [ 149 ] fabricated self‐supported and quantitatively substituted V 0.28 Co 2.72 C/CNFs with larger amounts via direct electrospinning. The electron transfer from V to Co made Co a local negative charge center and led to a significant increase in efficiency for overall water splitting.…”
Section: Electrospun Nanocatalysts For Electrochemical Water Splittingmentioning
confidence: 99%
“…By using such electrocatalysts as both cathode and anode, low‐cost water splitting electrolyzer can be realized, which avoids the usage of different equipment and processes for the different types of HER and OER electrocatalysts. Similarly, to enhance the overall water splitting performance, the electronic modulation and interface engineering of the electrocatalysts are also desirable 199‐213 …”
Section: Electrocatalytic Water Splitting Based On the Electrospun Namentioning
confidence: 99%
“…By the substitution of the cobalt with low‐electronegativity vanadium, the electronic structure of the Co 3 C could be tuned, exhibiting a lattice distortion (Figure 9A,B). 205 DFT calculations revealed that the V substitution made Co 3 C as the rich electronic center, which could weaken OH bonds and reduce the barrier for the OER process (Figure 9C,D). As a result, the prepared V 0.28 Co 2.72 C with 9 at.% V substitution showed both excellent HER and OER efficiency, delivering overpotentials of 87 and 210 mV to reach a current density of 10 mA cm −2 in an alkaline electrolyte, respectively.…”
Section: Electrocatalytic Water Splitting Based On the Electrospun Namentioning
confidence: 99%
See 2 more Smart Citations